Practical Policy in Pusong Slums Area, Lhokseumawe Methodology: Critical Pragmatism - Utaberta, Nangkula; ., Deni (International Journal of Engineering and Technology, 2019)
Nowadays, conditions of Pusong fisherman’s community (kampung) which is trapped in slump and poverty arise as major issues in Lhokseumawe. Over the years, this phenomenon tends to increase and spread out in the area of kampung. Concerning to the phenomenon, the study was conducted to reveal the existence of occupants within their environment. Practical observation was held to conceive the way of life of the people in the kampung. The results of study are expected to be used by the local government to make policy regarding to the kampung improvement. Research findings indicate that idea of ‘rubbish bank’ can be adopted as ‘pioneer’ policy to improve the kampung’s environment become preferable.